FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN DALAM PENGENDALIAN DIABETES MELLITUS DI PUSKESMAS MAPADDEGAT - Pelani, Helman; Eliza, Eliza; Nelli, Septa; Wati, Linda Diana (Universitas Fort De Kock, 2024)
ABSTRACT Diabetes Mellitus is a chronic metabolic disease where diabetics cannot produce sufficient amounts of insulin or the body is unable to use insulin effectively. The acute complications of DM are diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic status (SHH). The aim of the research is to determine the factors associated with compliance in controlling diabetes mellitus at the Mapaddegat Health Center in 2023. This type of research is analytical descriptive which was carried out at the Mapaddegat Health Center in July-August 2023, with a total sample size of 56 people. Data were analyzed using univariate and bivariate data with SPSS Chi Square to see the relationship between each variable. The results of the univariate analysis showed that most (55.4%) of the respondents had poor eating patterns, more than half (51.8%) of the respondents were irregular in taking medication, more than half (55.4%) of the respondents were not compliant in controlling diabetes mellitus. . The results of the bivariate analysis showed a relationship between eating patterns and compliance in controlling diabetes mellitus, pValue = 0.015 (p<0.05) OR 1.971, a relationship between exercise habits and compliance in controlling diabetes mellitus, pValue = 0.007 (p<0.05) OR 2.017 , the relationship between taking medication and compliance with Diabetes Mellitus control pValue = 0,000 (p<0.05) OR 3.879. The conclusion is that there is a relationship between eating patterns, exercise habits, taking medication and compliance with diabetes mellitus control at the Mapaddegat Community Health Center in 2023. It is hoped that health workers and nutritionists can always increase the visit schedule for diabetes mellitus sufferers and also provide consultations about nutrition and diet for diabetes sufferers. mellitus.Keywords : Compliance, Control, Diabetes MellitusABSTRAK Diabetes Mellitus merupakan penyakit metabolik yang berlangsung kronik dimana penderita diabetes tidak bisa memproduksi insulin dalam jumlah yang cukup atau tubuh tidak mampu menggunakan insulin secara efektif. Keadaan komplikasi akut DM adalah ketoasidosis diabetik (KAD) dan Status Hiperglikemi Hiperosmolar (SHH). Tujuan penelitian untuk mengetahui faktor-faktor yang berhubungan dengan kepatuhan dalam pengendalian diabetes mellitus di Puskesmas Mapaddegat Tahun 2023. Jenis penelitian ini adalah deskriptif analitik yang dilaksanakan di Puskesmas Mapaddegat pada bulan Juli-Agustus 2023, dengan jumlah sampel total sampel yaitu 56 orang. Data dianalisis menggunakan data univariat dan bivariat dengan SPSS Chi Square untuk melihat hubungan pada masing-masing variabel. Hasil analisis univariat didapatkan sebagian besar (55,4 %) responden memiliki pola makan buruk, lebih dari separoh (51,8 %) responden tidak teratur dalam minum obat, lebih dari separoh (55,4 %) responden tidak patuh dalam pengendalian diabetes melitus. Hasil analisis bivariat ada hubungan pola makan dengan kepatuhan dalam pengendalian diabetes mellitus pValue = 0, 015 (p<0,05) OR 1,971,hubungan kebiasaan olahraga dengan kepatuhan pengendalian diabetes mellitus pValue = 0, 007 (p<0,05) OR 2,017, hubungan minum obat dengan kepatuhan pengendalian Diabetes Mellitus pValue = 0, 000 (p<0,05) OR 3,879. Kesimpulan ada hubungan pola makan, kebiasaan olahraga, minum obat dengan kepatuhan pengendalian Diabetes Mellitus di Puskesmas Mapaddegat Tahun 2023.Diharapkan kepada petugas kesehatan, ahli gizi agar dapat selalu meningkatkan jadwal kunjungan pada penderita diabetes melitus dan juga memberikan konsultasi tentang gizi dan diet bagi penderita diabetes melitus.Kata Kunci : Kepatuhan, Pengendalian, Diabetes Melitus